Research Progress on Biotransformation of Agri-food Lignocellulosic Biomass Waste into Vanillin - ZHOU Man, LI Chenglin, LIN Kailin, CHEN Luyi, WANG Ziyi, YANG Xinying, JIANG Haiyan, ZHANG Xiaoxue, HUANG Xiaoqi, ZHOU Cunshan (Shipin Kexue)
Vanillin is one of the most in-demand spices in the world, which is widely used in various industries such as food, medicinal, and chemical industries. The process of extracting natural vanillin from plants is cumbersome with a limited yield. The chemical synthesis of vanillin faces several issues such as insufficient quality and safety. Microbial transformation is safe and efficient, making it suitable for large-scale production of vanillin. In recent years, due to energy shortages, resource scarcity, and environmental pollution, there has been a rapid development in the production of vanillin by the biotransformation of low-cost, widely available, and renewable agri-food lignocellulosic biomass waste as substrates. This article introduces the types and sources of commercial vanillin, the biotransformation pathway of lignin into vanillin by a process termed biological funneling, and the biosynthesis pathway of vanillin using lignin-derived compounds and glucose as fermentation substrates. It reviews recent progress on the microbial transformation of agri-food lignocellulosic biomass waste into vanillin from three perspectives: strain screening, optimization of cultivation conditions, and metabolic engineering to enhance vanillin production. Moreover, the challenges and potential solutions for current research are discussed. This article will provide valuable guidance for the production of vanillin through the biotransformation of agri-food lignocellulosic biomass waste.